Comparative Efficacy of Unilateral vs. Bilateral Approaches in Percutaneous Kyphoplasty and Vertebroplasty for Osteoporotic Vertebral Compression Fractures - Cine, Hidayet Safak; Uysal, Ece; Aladdam, Mohammed; Herdan, Emre; Gunaydin, Mehmet Emre; Demir, Huseyin; Karaarslan, Numan (Indian Journal of Neurosurgery, 2024)
Osteoporotic vertebral compression fractures (OVCFs) significantly affect the quality of life of elderly patients by causing severe pain and functional loss. Percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP) are minimally invasive surgical techniques for the treatment of OVCFs. It can be performed unilaterally or bilaterally for prevention of kyphosis without morbidity. This study aims to compare the radiological and clinical outcomes of unilateral versus bilateral approaches in PKP/PVP procedures.This retrospective observational study included 230 unilateral (n = 110) and bilateral (n = 120) patients from three spinal centers who underwent PCP or PVP for OVCF treatment between 2018 and 2024. During the operation, operative time, cement volume, and frequency of fluoroscopy were recorded. The duration of hospital stay was recorded. Visual Analog Scale (VAS) scores and Oswestry Disability Index (ODI) scores were used for clinical evaluation at preoperative, postoperative day 1, and final follow-up. Vertebral height and kyphotic angle were used for radiological evaluation.The unilateral approach had significantly shorter operative times (43.4 ± 9.01 minutes, p < 0.001) compared to the bilateral approach (59.9 ± 11.5 minutes), required less cement (4.44 ± 1.01 mL vs. 7.53 ± 0.911 mL, p < 0.001), and had fewer fluoroscopy (26.2 ± 6.58 vs. 55.6 ± 9.98, p < 0.001). There were no significant differences between the two groups in VAS scores (p = 0.663), ODI scores (p = 0.650), vertebral height restoration (p = 0.720), or kyphotic angle correction (p = 0.129). However, the bilateral group had a higher rate of cement leakage (35 vs. 12%, p = 0.035).These findings suggest that the unilateral approach offers procedural advantages without compromising clinical efficacy, making it a preferable option for elderly patients with OVCFs.
Keywords: bilateral approach; osteoporotic vertebral compression fractures; percutaneous kyphoplasty; vertebroplasty; unilateral approach